2016
DOI: 10.18699/vj16.205
|View full text |Cite
|
Sign up to set email alerts
|

The impact of terahertz radiation on an extremophilic archaean Halorubrum saccharovorum proteome

Abstract: Nonthermal effects of terahertz radiation on living objects are currently intensely studied, as more sources of this radiation type and devices employing it are being constructed. Terahertz radiation is increasing ly used in security and inspection systems, medical and scientific appliances due to its low quant energy, which does not cause severe effects on organisms as other radiation types with higher quant energies do. The aim of this study was the identification of pro tein complexes participating in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This observation was confirmed by the rapid and sustained activation of the cellular systems that compensate for the inhibition of the respiratory and glycolytic systems, namely the upregulation of ATP synthase and of a wide range of enzymes that generate NADH. With regards to the translation system, a similar effect was previously shown when cells of the thermostable archaea Halorubrum saccharovorum were exposed to long-term, non-thermal THz radiation (2.3 THz, 5 h), where the expression of genes encoding the structure of translation initiation and elongation factors was also reduced by irradiation [ 63 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This observation was confirmed by the rapid and sustained activation of the cellular systems that compensate for the inhibition of the respiratory and glycolytic systems, namely the upregulation of ATP synthase and of a wide range of enzymes that generate NADH. With regards to the translation system, a similar effect was previously shown when cells of the thermostable archaea Halorubrum saccharovorum were exposed to long-term, non-thermal THz radiation (2.3 THz, 5 h), where the expression of genes encoding the structure of translation initiation and elongation factors was also reduced by irradiation [ 63 ].…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, it was shown that ATPase HslU, being a molecular chaperon, prevents cell growth inhibitor SulA aggregation and its elimination via HslV-mediated degradation [ 59 , 63 ]. Cell growth deceleration may be a consequence of the increased concentration of HslU during THz irradiation.…”
Section: Discussionmentioning
confidence: 99%